Identification of Distinct Immune Subtypes in Colorectal Cancer Based on the Stromal Compartment - Shen, Rongfang; Li, Ping; Li, Bing; Zhang, Botao; Feng, Lin; Cheng, Shujun (Frontiers in Oncology, 2020)
The tumor environment is of vital importance for the incidence and development of colorectal cancer. Increasing evidence in recent years has elaborate the vital role of tumor environment in cancer-subtype classification and patients’ prognosis, but a comprehensive understanding of the colorectal tumor environment purely depending on stromal compartment is lacking. To decipher the tumor environment features of colorectal cancer and explore the role of its immune context composition in cancer classification, we performed a gene expression microarray on microdissection-processed stromal compartments of colorectal cancer and adjacent normal tissues. Through the integrated analysis of our data with public gene expression microarray data of microdissection-processed stromal and epithelial colorectal cancer tissues, we first identified four highly connected gene modules representing biological features of four tissue compartments by applying weighted gene coexpression network analysis algorithm and classified colorectal cancers into three immune subtypes by adopting nearest template prediction algorithm. Systematical analysis of the four identified modules mainly reflected the closely interplay between the biological changes of intrinsic and extrinsic characteristics at the initiation of colorectal cancer. And the colorectal cancers were stratified into three immune subtypes based on gene template identified from representative gene modules of the stromal compartment: the active immune, active stroma and mixed type subtypes. These immune subtypes differed by immune cell infiltration pattern, expression of immune checkpoint inhibitors, mutation landscape, extent of mutation burden, extent of copy number burden, prognosis and chemotherapeutic sensitivity. Further analysis indicated that the activation of NF-kB signaling pathway was the major mechanism causing the no immune infiltration milieu in active stroma subtype and inhibitors on NF-kB signaling pathway would be candidate drug treating active stroma patients. Overall, the results suggest that characterizing colorectal cancer by the tumor environment is of vital importance in predicting patients’ clinical outcomes and helping guide precision and personalized management.